Successful treatment of lichen striatus with co2 fractional laser and photodynamic therapy: A case report - Lyu, Shuang; Liu, Chang; Fu, Xi’an; Liu, Hong; Zhang, Furen (Photodiagnosis and photodynamic therapy, 2025)
•Combined CO₂ fractional laser and ALA-PDT achieved rapid remission in lichen striatus.•Hyperpigmentation was linked to parameter selection with no recurrence observed.•Optimized protocols derived from current parameters may enhance efficacy and minimize adverse effects.•Confocal microscopy visualized the resolution of inflammatory lesions and post-inflammatory hyperpigmentation during the recovery. This case report describes the successful treatment of lichen striatus (LS) with a combination of 5-aminolevulinic acid photodynamic therapy (ALA-PDT) and fractional CO₂ laser (CO₂FL). LS, a self-limiting inflammatory dermatosis, often causes cosmetic concerns and psychological distress, with current therapies showing variable efficacy. An 18-year-old female patient with LS on the left upper back received two rounds of combined treatment at one-month intervals. Confocal microscopy confirmed the absence of inflammatory lesions and showed post-inflammatory hyperpigmentation, likely caused by treatment parameters (CO₂FL: 50 W, 1.2 mm spot spacing; 20 % ALA-PDT for 120 min). Clinically, lesions completely subsided within nine months with no recurrence. This combination therapy achieved rapid remission, though hyperpigmentation highlights the need for parameter optimization, such as reducing ALA concentration to 10 % as suggested in relevant studies. The study provides detailed treatment parameters, but future controlled trials with quantitative measures (e.g., lesion size, pre-/post-treatment symptom scores for pruritus) are needed for objective efficacy evaluation.